Analysis of Online Ticket Sales Procedures at Super Air Jet Airline in Soekarno-Hatta International Airport - Mu’arifin, Hidayatul; Dewi, Ririn Sari; Rahmawati, Titah (Sean Institute, 2025)
This study explores the procedures of online ticket sales at Super Air Jet operating through Soekarno-Hatta International Airport. The research applies a descriptive qualitative approach to examine the flow of booking, payment, and ticket issuance as well as the internal control mechanisms involved. Data were collected through observation, interviews, and documentation, allowing a comprehensive view of the system’s effectiveness. The findings reveal that the online ticketing process has been implemented efficiently and is aligned with industry standards for low-cost carriers, providing convenience for passengers. Nevertheless, challenges remain, particularly in digital literacy among users and the need to strengthen internal control activities such as separation of duties, monitoring, and reconciliation. The study highlights the importance of integrating performance metrics and control frameworks to enhance reliability, mitigate risks, and improve customer satisfaction. These insights contribute to better understanding of digital ticketing practices in the aviation sector.